2019
DOI: 10.1016/j.tim.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The Promise of Long-Acting Antiretroviral Therapies: From Need to Manufacture

Abstract: Antiretroviral therapy has transformed human immunodeficiency virus infections from certain death to a manageable chronic disease. Achieving strict adherence to drug regimens that limit toxicities and viral resistance are achievable goals. Success is defined by halting viral transmission and by continuous viral restriction. A step towards improving treatment outcomes is in long acting antiretrovirals. While early results remain encouraging there remain opportunities for improvement. These rest, in part, on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 121 publications
0
20
0
Order By: Relevance
“…However viral control is linked to regimen adherence affected by disease co-morbidity, stigma, behavior, illicit drug-use, and cost 1 . Such limitations were the impetus towards the development of long-acting (LA) injectables 2 , 3 , 4 , 5 , 6 . In April, 2019, ViiV Healthcare submitted a New Drug Application to the US Food and Drug Administration (FDA) for monthly cabotegravir and rilpivirine (CAB and RPV) injectables applied in HIV-1 treatments 7 .…”
mentioning
confidence: 99%
“…However viral control is linked to regimen adherence affected by disease co-morbidity, stigma, behavior, illicit drug-use, and cost 1 . Such limitations were the impetus towards the development of long-acting (LA) injectables 2 , 3 , 4 , 5 , 6 . In April, 2019, ViiV Healthcare submitted a New Drug Application to the US Food and Drug Administration (FDA) for monthly cabotegravir and rilpivirine (CAB and RPV) injectables applied in HIV-1 treatments 7 .…”
mentioning
confidence: 99%
“…The ability to sustain plasma and tissue drug levels beyond the plasma 90% inhibitory concentration (IC 90 ) for months would reduce pill burdens, increase regimen adherence and reduce adverse events that plague current medications. This would also lift the psychological stigma for strict daily regimens reminding patients of disease and impacting mental health 16, 39, 40. To simplify measurements of LA ARV efficacy by pharmacokinetic (PK) and biodistribution (BD) tests and optimize dosing, theranostics was introduced 16.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, a number of challenges exist to implement such regimens. These include, but are not limited to, required dosing volumes, frequencies of injection, untoward side effects, and maintenance of antiretroviral efficacy 16-18. Even more importantly, only two LA ARVs are currently in the pipeline 12.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutics approved for HBV mainly include nucleos(t)ide analogues inhibitors of RT, two of which (tenofovir and lamivudine) also have anti-HIV activity. She reported that Long-Acting Slow Effective Release antiretroviral therapeutics (LASER ART) control HBV replication in the liver of humanized mice [11,12]. In rats, a single injection of 75 mg/kg nanoformulated lamivudine persisted for 28 days in the peripheral blood with significant accumulation in spleen, liver, and lymph nodes.…”
Section: Session 2: Hepatitis Viruses (Hbv Hcv) and Hiv-hepatitis VImentioning
confidence: 99%